The effects of hiring credits on firm dynamics: a synthetic difference-in-differences evaluation - Edoardo Santoni; Fabrizio Patriarca; Margherita Scarlato (Global Labor Organization (GLO), 2024)
Despite hiring credits being a long-standing labor market policy, evidence of their impact at the firm level is limited. This paper contributes to the existing literature by providing an empirical analysis of an untargeted hiring credits policy introduced in Italy in 2015. We implement the Synthetic Control Difference in Differences method using administrative employer-employee data. The results show an increase in employment but at the same time a reduction in capital intensity, labor productivity and workforce quality. Furthermore, the reduction in labor costs for involved firms is not associated with an increase in their profitability.
Keywords: J21; J08; D22; 330; hiring credits; synthetic difference-in-differences; firm performance